Legalitas Rangkap Jabatan Direksi Dan Dewan Komisaris Pada Badan Usaha Milik Negara Yang Berbentuk Perseroan Terbatas - Risanti Suci Pratiwi (Lex Renaissance, 2019)
Limited Liability Company (PT) is a common form and is widely used in the business world in Indonesia. As a legal entity means that the company is an independent subject. This means that a PT can carry out business activities on its own behalf like humans, have their own wealth, and can be sued or sued before the court. Even so, PT needs organs that can represent itself to do all of these functions. The organs of PT in question are the general meeting of shareholders (GMS), the directors and the board of commissioners. In carrying out their duties, the three organs of PT above must act in accordance with the interests and objectives of the company so that the actions taken by the organs would not harm the company. The practice of concurrent positions of the directors and board of commissioners is a form of management behavior that is considered as a monopolistic practice. This study concludes that concurrent positions is a practice that is prohibited according to the statutory regulations even though it is not clearly regulated in the Company Law, yet in other regulations such as in the Law on State-Owned Enterprises (BUMN), concurrent positions are indeed prohibited.